Pengaruh Lingkungan Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS Kelas VIII di SMP Negeri 4 Malingping - Arif Rahman Hakim; Nadia Rista; Dermawan Dermawan (Neolectura, 2021)
Education is an important thing in life. There are three components of education that are intended to achieve educational goals. In simple terms, the basic purpose of education can be assessed from student achievement. however, SMP Negeri 4 Malingping shows low learning achievement. There are many factors that influence the low learning achievement of students at SMP Negeri 4 Malingping. One of the factors is the environment, especially the learning environment. For this reason, researchers want to know whether the learning environment can affect student achievement in SMP Negeri 4 Malingping. This research is quantitative with the research method used is causal associative. This research was conducted at SMP Negeri 4 Malingping which is located at Kp. Sangiang, RT. 001/006, Sangiang Village, Malingping District, Lebak Regency, Banten. The research was carried out for 5 months, starting from October 2018 to February 2019. The total population and sample of the study were 65 students of class VIII. Data collection techniques in the form of observation. The data source used is primary data. There is a positive and significant influence between the variables of the school environment on student achievement at SMPN 4 Malingping.